'Edison's Telephonoscope': the visual telephone and the satire of electric light mania. Issue 1 (2nd January 2017) - Roberts, Ivy
Abstract: For the past 30 years, media historians have consistently interpreted George Du Maurier's 'Edison's Telephonoscope' ( Punch, 1878) as a depiction of television. Scholars treat the illustration as a literary document conveying an image of what Victorians thought television one day might become. But this interpretation is incomplete because it neglects the multiplicity of frames of reference readers bring to the image. Leafing through the December 9 issue of Punch in context strikes the reader with a very different impression of the 'Telephonoscope.' Du Maurier's title resonated with readers, who would have recognised the distance-hearing-and-speaking device not as a visual telephone but in connection with the much-ridiculed 'ear telescope, ' or megaphone, that Edison had tried to promote earlier in the year. Other memorable caricatures, including the 'Museum of Modern Invention' and 'Edison's Anti-Gravity Underclothing, ' appeared on adjacent pages to 'Edison's Telephonoscope.' Punch 's cartoon could be read as a satire of Edison's public image: a statement against technological innovation. This article urges readers to look past surface appearance by examining the reception of 'Edison's Telephonoscope, ' along with the phonograph, megaphone and electric light. By establishing connections to other 1878 events, Edisonian inventions and the misunderstandings that arose from communicating across the Atlantic, this article argues for an interdisciplinary approach that acknowledges the contexts in which cultural representations circulated.